2022
DOI: 10.55043/jaast.v6i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield, and Fiber Morphology of Kenaf (Hibiscus Cannabinus L.) Varieties Influenced by Different Levels of Npk Fertilizers

Abstract: Different levels of NPK fertilizer were used to improve the growth, yield, and fiber morphology of two kenaf varieties. Therefore, a field experiment was conducted in the summer season of 2021 at the Grdarasha Field, College of Agricultural Engineering Sciences, Salahaddin University-Erbil. The results revealed that adding NPK at the rate of 100 kg/ha caused improved growth and yield characteristics includes; plant height, stem diameter, leaf number, and total fresh stem yield by almost (3.35 m, 25.88 mm, 250.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(2018) found that Mg 2+ delayed post-harvest deterioration in cassava. Similarly, kenaf plants exhibited enhanced growth when exposed to Mg 2+ , as documented by Salih et al. (2023) .…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 77%
See 1 more Smart Citation
“…(2018) found that Mg 2+ delayed post-harvest deterioration in cassava. Similarly, kenaf plants exhibited enhanced growth when exposed to Mg 2+ , as documented by Salih et al. (2023) .…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 77%
“…For instance, Djabou et al (2018) found that Mg 2+ delayed post-harvest deterioration in cassava. Similarly, kenaf plants exhibited enhanced growth when exposed to Mg 2+ , as documented by Salih et al (2023). Watermelon genetics were also affected, with a distinct gene expression pattern in response to Mg 2+ , according to Heidari et al (2022).…”
Section: Effects Of Magnesium On Crop Qualitymentioning
confidence: 94%